A cognitive semantic analysis of metaphors of innovation in education in Lim Kok Wing’s writings - Razali, Nor Asiah (2020)
In this day and age, innovation is not an alien concept. It is prevalent in our spheres of life and it has been discussed in varied disciplines, including education. The discussion on innovation in the context of education has been published in various documents, such as educational magazines, books and blogs. One example of such a documentation is the writings on innovation by a renowned figure associated with innovation in education, namely, Tan Sri Dr Lim Kok Wing, compiled in a book titled “The Future is Coming”. In education, innovation is required to transform the education system to prepare the future generation to be future- ready for innovation-driven economy. In this light, various studies were conducted to examine the importance of innovation towards people, society, organisation and the world. Despite the importance of innovation, people are still struggling to adopt and adapt innovation in their life due to the lack of comprehension toward the concept. Therefore, it is important to examine the concept of innovation particularly through the metaphorical expressions in order to investigate peoples’ conception, perspectives and belief toward the concept of innovation specifically in the current education landscape of Malaysia. This study investigates the conceptualisation of innovation in the context of education through the writings of Tan Sri Dr Lim Kok Wing. Specifically, it aimed 1) to unravel the conceptual metaphors of innovation in the context of education and 2) to examine how the unravelled metaphors reflect his conceptions of innovation in education. In total, 42 written texts on innovation by Tan Sri Lim Kok Wing, published in the book “The Future is Coming” were included as data of the study. The data were analysed using Lakoff and Johnson’s (1980) Conceptual Metaphor Theory. Findings of the study unravelled seven salient conceptual metaphors underlying the expressions related to innovation in education. These metaphors involve the mappings of the source domains of JOURNEY, WAR, OBJECT, HUMAN BEING, SPORT, BUILDING, and FORCE to the target domain of INNOVATION. In addition, two salient conceptual metaphors, namely, INNOVATION IS A JOURNEY and TO INNOVATE IS TO MOVE were identified. The unravelled metaphors underlying the writings on innovation suggest that innovation is conceived as a long process which requires careful planning. It is also conceived as a sport, in which the aspects of competition, teamwork and effort are highlighted. The findings of the study provide insight into how innovation is conceived, specifically from the lens of Lim Kok Wing which would be beneficial for the audience to have a better comprehension on innovation.